Cascaded Wx: A Novel Prognosis-Related Feature Selection Framework in Human Lung Adenocarcinoma Transcriptomes - Shin, Bonggun; Park, Sungsoo; Hong, Ji Hyung; An, Ho Jung; Chun, Sang Hoon; Kang, Kilsoo; Ahn, Young-Ho; Ko, Yoon Ho; Kang, Keunsoo (Frontiers in Genetics, 2019)
Artificial neural network-based analysis has recently been used to predict clinical outcomes in patients with solid cancers, including lung cancer. However, the majority of algorithms were not originally developed to identify genes associated with patients' prognoses. To address this issue, we developed a novel prognosis-related feature selection framework called Cascaded Wx (CWx). The CWx framework ranks features according to the survival of a given cohort, by training neural networks with three different high- and row-risk groups in a cascaded fashion. We showed that this approach accurately identified features which best identify the patients' prognoses, as compared to other feature selection algorithms, including the cox proportional hazard and Coxnet models, when applied to the cancer genome atlas (TCGA) lung adenocarcinoma (LUAD) transcriptome data. The prognostic potential of the top 100 genes identified by CWx outperformed or was comparable to those identified by the other methods as assessed by concordance index (c-index). In addition, the top 100 genes identified by CWx were found to be associated with the Wnt signaling pathway, providing biologically relevant evidence for the value of these genes in predicting the prognosis of patients with LUAD. Further analyses of other cancer types showed that the genes identified by CWx had the highest prognostic values according to c-index. Collectively, the CWx framework will potentially be of great use to prognosis-related biomarker discoveries in a variety of diseases.